An investigation of EFL Students’ Ability in Writing Discussion Text Using Feedback in Blended Learning Model - Saiful Latif; Abdulhalim Daud (International Journal of Education, Information Technology, and Others, 2023)
Writing is a language skill that should be learned by university students. It is sometimes the students get difficulties collecting ideas, how to organize the ideas, and where to start writing. This study aims to describe the EFL Students’ Ability in Writing Discussion Text Using Feedback in Blended Learning. This study used qualitative description. The participant of this research are 40 fresh students university students at one of the universities in North Maluku and three fresh university students’ writing drafts were collected to be analyzed. The students were categorized into low achievers, middle achievers, and high achievers. The result shows that the students learn to write through the blended Learning Model and gets feedback that made a great change in their writing.